2006
DOI: 10.1017/s1473550406003363
|View full text |Cite
|
Sign up to set email alerts
|

UV-Vis spectroscopy of stardust

Abstract: : NASA's Stardust mission flew through the coma of comet Wild 2 in January 2004, capturing dust grains as it did so. The grains were returned safely to Earth in January 2006, and are in the process of being distributed to investigators. As members of the Spectroscopy Preliminary Examination Team, we are preparing to analyse Stardust grains. Our contribution is to measure the spectrum of the grains between 200 nm (in the near ultraviolet) and 800 nm (near infrared). The purpose of the measurement is to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Since the film thickness is not monitored precisely, the nature of plots cannot be quantitatively explained in this study. However, the presence of sharper peaks can be qualitatively described as arising from the presence of aerogel particulates in the samples since a similar peak below 250nm is also seen in the work of Fernandes et al (29) for the aerogel samples. Therefore, it is suggested that the sharper peaks of the composite samples in the present study indicate the existence of aerogel within the material at the end of the curing cycle.…”
Section: Optical Transmittance and Scattering Characteristicssupporting
confidence: 61%
“…Since the film thickness is not monitored precisely, the nature of plots cannot be quantitatively explained in this study. However, the presence of sharper peaks can be qualitatively described as arising from the presence of aerogel particulates in the samples since a similar peak below 250nm is also seen in the work of Fernandes et al (29) for the aerogel samples. Therefore, it is suggested that the sharper peaks of the composite samples in the present study indicate the existence of aerogel within the material at the end of the curing cycle.…”
Section: Optical Transmittance and Scattering Characteristicssupporting
confidence: 61%